Perception of community pharmacists towards the barriers to enhanced pharmacy services in the healthcare system of Dubai: a quantitative approach - Rayes IK; Hassali MA; Abduelkarem AR (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Background: In many developing countries, pharmacists are facing many challenges while they try to enhance the quality of services provided to patients approaching community pharmacies. Objective: To explore perception of community pharmacists in Dubai regarding the obstacles to enhanced pharmacy services using a part of the results from a nation-wide quantitative survey. Methods: A questionnaire was distributed to 281 full-time licensed community pharmacists in Dubai. The questionnaire had 5 inter-linked sections: demographic information, information about the pharmacy, interaction with physicians, pharmacists' current professional role, and barriers to enhanced pharmacy services. Results: About half of the respondents (45.4%, n=90) agreed that pharmacy clients under-estimate them and 52.5% (n=104) felt the same by physicians. About 47.5% (n=94) of the respondents felt that they are legally unprotected against profession's malpractice. Moreover, 64.7% (n=128) stated that pharmacy practice in Dubai turned to be business-focused. In addition, 76.8% (n=252) found that one of the major barriers to enhanced pharmacy services is the high business running cost. Pharmacists screened tried to prove that they are not one of the barriers to optimized pharmacy services as 62.7% (n=124) disagreed that they lack appropriate knowledge needed to serve community and 67.7% (n=134) gave the same response when asked whether pharmacy staff lack confidence when treating consumers or not. Conclusions: Although being well established within the community, pharmacists in Dubai negatively perceived their own professional role. They stated that there are number of barriers which hinder optimized delivery of pharmacy services like under-estimation by pharmacy clients and other healthcare professionals, pressure to make sales, and high running cost.